2011
DOI: 10.1371/journal.pone.0019719
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Association Study for Atopy and Allergic Rhinitis in a Singapore Chinese Population

Abstract: Allergic rhinitis (AR) is an atopic disease which affects about 600 million people worldwide and results from a complex interplay between genetic and environmental factors. However genetic association studies on known candidate genes yielded variable results. The aim of this study is to identify the genetic variants that influence predisposition towards allergic rhinitis in an ethnic Chinese population in Singapore using a genome-wide association study (GWAS) approach. A total of 4461 ethnic Chinese volunteers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
72
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 81 publications
(79 citation statements)
references
References 57 publications
(78 reference statements)
5
72
0
2
Order By: Relevance
“…Using our GWAS data we also replicated previously identified SNPs through asthma GWAS in our population for both atopy and AR phenotype [19]. SNPs from HLA-DQB1, HLA-DRB1, GRIN2B, ACO1, HLA-DQA2, CA10, FAM82A, HIVEP3, SMAD2, PIP-3E and NPSR1 were shown to be associated to atopy and AR albeit not reaching the genome-wide threshold of 5 × 10 -8 .…”
Section: Introductionsupporting
confidence: 80%
“…Using our GWAS data we also replicated previously identified SNPs through asthma GWAS in our population for both atopy and AR phenotype [19]. SNPs from HLA-DQB1, HLA-DRB1, GRIN2B, ACO1, HLA-DQA2, CA10, FAM82A, HIVEP3, SMAD2, PIP-3E and NPSR1 were shown to be associated to atopy and AR albeit not reaching the genome-wide threshold of 5 × 10 -8 .…”
Section: Introductionsupporting
confidence: 80%
“…The first one by Andiappan et al identified suggestive associations with two SNPs on the MRPL4 and BCAP genes in a Chinese cohort; both genes have putative roles in inflammatory/immune response pathways. 165 However, none of these SNPs reached genome-wide significance. In the second GWAS meta-analysis of AR by Ramasamy et al, a SNP in a locus situated between chromosome 11 open reading frame 30 (C11orf30) and leucine-rich repeat containing 32 (LRRC32) attained genome-wide significance.…”
Section: Gene-environment Interactions In Atopic Disordersmentioning
confidence: 99%
“…The few exceptions were cases of classical linkage analysis. In 2011 a genome-wide association study (GWAS) [4] and a GWAS meta-study [5] were published in addition to a number of candidate gene studies. Thus, the current list of implicated SNPs is clearly dominated by results from early candidate gene studies.…”
Section: Introductionmentioning
confidence: 99%